Preparation Process, Sensory Profile And Chemical Composition of Sargyangma. - Limbu, Prem Kumar; Acharya, Devraj; Subba, Dilip (Journal of Food Science and Technology Nepal, 2018)
The aim of present work was to describe the traditional process of preparation, sensory profile and chemical composition of Sargyangma. Sargyangma was prepared in lab and its descriptive sensory test and chemical analysis were performed. The colour of Sargyangma was slightly brown and unevenly distributed. Sargyangma had characteristic aroma and taste mainly due to cooked blood and Yangben. Yangben is local word used by Limbu ethnic community for edible lichen. This had moderately intense bloody aroma and taste. Very intense Yangben aroma and taste was readily detectable. In the overall, Sargyangma had moderately intense pleasant, porky-meaty, spicy aroma. Sargyangma was moderately compact and juicy. Sargyangma contained high amount of fat (29.2%) and moderate amount of protein (13.33%).